CHAMPS CULTURE TO INCREASE EMPLOYEE PERFORMANCE - Aldri Frinaldi; Muhammad Ali Embi; Aziza Bila (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2019)
The objective of this study was to determine the influence of corporate culture in improving employees' performance at state-owned enterprise PT. Semen Padang, West Sumatra. This research used quantitative methods and was supported by qualitative data. Data were collected quantitatively from samples selected using Simple Random Sampling. Qualitative data was collected with observation and interview with purposive sampling technique. The population of PT. Semen Padang employees are 1924 people. The sample was calculated using Slovin's formula (error of 5%) and consisted of 331 samples. The initial hypothesis in this research consisted of seven hypotheses. This study found a significant influence of a corporate culture that consists of six variables of work culture in improving employees’ performance at PT. Semen Padang. This study also found other factors that affect employees' performance. This study offers managers at PT. Semen Padang the key to increasing their employees' performance. The essence of this study is to prove that there is a significant influence of corporate cultures in improving employees' performance.